NANOMODIFIED CONCRETE - B. M. Khroustalev; V. V. Yaglov; Ya. N. Kovalev; V. N. Romaniuk; G. A. Burak; A. A. Mezhentsev; N. S. Gurinenko (Наука и техника)
One of the main directions in construction material science is the development of  next generation concrete that is ultra-dense, high-strength, ultra-porous, high heat efficient, extra corrosion-resistant. Selection of such direction is caused by extreme operational impacts on the concrete, namely: continuously increasing load on the concrete and various dynamics of such loads; the necessity in operation of concrete products in a wide temperature range and their exposure to various chemical and physical effects.The next generation concrete represents high-tech concrete mixtures with additives that takes on and retain the required properties when hardening and being used under any operational conditions. A differential characteristic of the next generation concrete is its complexity that presumes usage of various mineral dispersed components, two- and three fractional fine and coarse aggregates, complex chemical additives, combinations of polymer and iron reinforcement.Design strength and performance properties level of the next generation concrete is achieved by high-quality selection of the composition, proper selection of manufacturing techniques, concrete curing, bringing the quality of concrete items to the required level of technical condition during the operational phase. However, directed formation of its structure is necessary in order to obtain high-tech concrete.Along with the traditional methods for regulation of the next generation concrete structure, modification of concrete while using silica nanoparticles is also considered as a perspective one because the concrete patterning occurs due to introduction of a binder in a mineral matrix. Due to this it is possible to obtain nano-modified materials with completely new properties.The main problem with the creation of nano-modified concrete is a uniform distribution of nano-materials in the volume of the cement matrix which is particularly important in the cases of adding a modifier in micro-quantities. An additional environment is required in order to solve this problem and the environment will form a continuous phase in the composite. This function can be performed by liquid or dispersed phase.